Effect of ethyl‐bridged diphenylphosphine oxide on flame retardancy and thermal properties of epoxy resin. (27th February 2020) - Wei, Zhenqian; Wu, Jun; Liu, Zongru; Gu, Yanan; Luan, Guifang; Sun, Hejing; Yu, Qing; Zhang, Sheng; Wang, Zhongwei
Abstract : Three commercialized flame retardants, 1, 2‐bis(diphenylphosphinoyl)ethane (EDPO), 6, 6‐(1, 2‐phenethyl)bis‐6H‐dibenz[c, e][1, 2]oxaphosphorin‐6, 6‐dioxide (HTP‐6123), and hexa‐phenoxy‐cyclotriphosphazene (HPCTP), were used to prepare the flame retardant diglycidyl ether of bisphenol A (DGEBA) epoxy resin (EP) under the same experimental conditions. The effects of T g, thermal stability, and water absorption properties of EP caused by the three flame retardants were investigated and compared, together with their flame retardant efficiency. Results showed that the introduction of the three flame retardants improved the flame retardant performance of EP but led to decreases in T g and decomposition temperature. EDPO showed higher flame retardant efficiency than the other two flame retardants. EP/EDPO showed higher thermal stability, better flame retardant performance, higher T g value, and lower water absorption than EP/HTP‐6123 and EP/HPCTP. The study discovered that EDPO and HTP‐6123 primarily act through the gas phase flame retardant mechanism, while HPCTP is primarily driven by the condensed phase mechanism.